FLYPAPER EFFECT: FENOMENA SERIAL WAKTU DAN LINTAS KABUPATEN KOTA DI JAWA TIMUR 2003-2013 - Oktavia, Deni (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2014)
The aims of local autonomy is to achieve local independence funding, so the interference of the central government decrease. Local governments have funding source from the own region revenues (PAD), which is used to finance expenditures and development. Regency or municipalities funding sources not only their PAD. Local governments also get help from central government transfers such block grant aid or transfer fund (DAU). In the course of the central government transfers actually become a disincentive for increased regional funding. Regions become more dependent on central government transfers rather than optimize their own revenues (PAD). There are has indications of asymmetric behavior in response to the transfer of central government. Region revenues (PAD) and the transfer fund (DAU) from central government is generally positive effect on the regional expenditure (BD). Results for the time series test indicates that occurred flypaper effect, Â indicated by DAU more significant influence on regional expenditure of the influence of the PAD.Â Regency or manucipalities in East Java generally done flypaper effect, BD response was greater from DAU components. Key words: region revenues, transfer fund, regional expenditure